Chills, fatigue, chest distress, and an abnormal increase in WBC, neutrophil, CRP, and PCT induced by terconazole: A case report - Li, Xuemei; Yang, Xiaohong; Wang, Kejing; Chen, Lin (International journal of clinical pharmacology and therapeutics, 2021)
The vaginal routes of administration of terconazole, a synthetic triazole derivative, is widely used by patients with uncomplicated vulvovaginal candidiasis (VVC). A 32-year-old woman suffered from chills, fatigue, and chest distress after receiving one 80-mg terconazole vaginal suppository for the treatment of uncomplicated VVC. Then, the symptom persisted for 10 hours until the residue of terconazole was removed, and the vagina was repeatedly washed with iodophor. In addition, white blood cell (WBC), neutrophil, C-reactive protein (CRP), and procalcitonin (PCT) were tested and showed marked increase when the patient visited our hospital again on the next day after the treatment with terconazole. Intriguingly, these parameters gradually decreased after a single dose of intravenous fluids (0.9% sodium chloride injection 500 mL and 10% glucose injection 500 mL) instead of the antibiotic therapy. On the third day, WBC and neutrophils returned to normal levels. Thus, according to the Naranjo adverse drug reaction probability scale, terconazole was the probable cause of the symptoms and the elevated WBC, neutrophil, CRP, and PCT. To date, this is the first report that chest distress, and at the same time, elevation of WBC, neutrophil, CRP, and PCT were caused by terconazole. This would be beneficial to avoid the overuse of antibiotics. Resolving the adverse drug reaction with drug removal and intravenous fluids would be beneficial to avoid the overuse of antibiotics. Resolving the adverse drug reaction with drug removal and intravenous fluids would be beneficial to avoid the overuse of antibiotics.